2008
DOI: 10.1074/jbc.m802749200
|View full text |Cite
|
Sign up to set email alerts
|

The RING Domain and First Zinc Finger of TRAF6 Coordinate Signaling by Interleukin-1, Lipopolysaccharide, and RANKL

Abstract: TRAF6, a crucial adaptor molecule in innate and adaptive immunity, contains three distinct functional domains. The C-terminal TRAF domain facilitates oligomerization and sequence-specific interaction with receptors or other adaptor proteins. In conjunction with the dimeric E2 enzyme Ubc13-Uev1A, the N-terminal RING domain of TRAF6 functions as an E3 ubiquitin (Ub) ligase that facilitates its own site-specific ubiquitination through the generation of a Lys-63-linked poly-Ub chain. This modification does not cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 31 publications
2
101
0
Order By: Relevance
“…Our observations are consistent with earlier reports describing the role of TRAF6 as a key ubiquitin ligase and TAK1 and NEMO as major ubiquitinated pilars that facilitate recruitment of signaling molecules (21,25). In support of this notion, recent evidence points to the paradigm that TRAF6-mediated ubiquitination is an important step for the formation and activation of a signaling complex that includes UBC13, TAK1, and its adaptors TAB1 and TAB2 (40,(45)(46)(47)(48). In a more recent study, Walsh et al, (42) showed that the RING finger of TRAF6 is required for the activation of TAK1, and TRAF6 was found to interact with TAK1.…”
Section: Discussionmentioning
confidence: 94%
“…Our observations are consistent with earlier reports describing the role of TRAF6 as a key ubiquitin ligase and TAK1 and NEMO as major ubiquitinated pilars that facilitate recruitment of signaling molecules (21,25). In support of this notion, recent evidence points to the paradigm that TRAF6-mediated ubiquitination is an important step for the formation and activation of a signaling complex that includes UBC13, TAK1, and its adaptors TAB1 and TAB2 (40,(45)(46)(47)(48). In a more recent study, Walsh et al, (42) showed that the RING finger of TRAF6 is required for the activation of TAK1, and TRAF6 was found to interact with TAK1.…”
Section: Discussionmentioning
confidence: 94%
“…MEFs derived from WT, Irgm1/m3 −/− , TRAF6 −/− , p62 −/− , and GBP chr3−/− mice were previously described (6,(59)(60)(61). Primary murine BMMs were isolated from the tibia and femurs of 2-4-mo-old mice as described before (10).…”
Section: Methodsmentioning
confidence: 99%
“…Other laboratories have reported that RANKL signaling cannot be restored to TRAF6 KO monocytes by the reexpression of TRAF6[C70A] (17,39). This could be related to the problem discussed in the preceding section in refolding this E3 ligase-inactive mutant in MEFs to a conformation that can support signaling.…”
Section: Il-1 Signaling In Mefs Frommentioning
confidence: 99%
“…Although truncated forms of TRAF6 lacking the really interesting new gene (RING) domain were reported to restore IL-1-signaling to TRAF6 knockout (KO) mouse embryonic fibroblasts (MEFs) many years ago (16), other laboratories reported subsequently that the E3 ligase-inactive TRAF6[C70A] mutant could not (12,17,18). These reports led to widespread acceptance of the notion that the E3 ligase activity of TRAF6 is essential for IL-1 signaling.…”
mentioning
confidence: 99%